A pre-polymer solution, a preparation method thereof, a lithium battery and an electric device

CN122685804APending Publication Date: 2026-09-04BTR NEW MATERIAL GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610931081.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

在现有的技术方案与实际操作中,通常未对这种内部组分比例的波动进行区分,而是将其作为单一组分直接投入使用,导致不同批次单体在聚合时的反应速率和形成的交联网络密度存在无序波动

Benefits of technology

[0017] Compared with existing technologies, the prepolymer liquid provided in this application precisely defines the molecular microstructure of the crosslinkable monomer composition, clearly specifying the mass fraction of pentaerythritol esters containing three and four acrylate groups, and strictly controlling their total to 80% or higher. This greatly suppresses the interference of component fluctuations caused by batch-to-batch differences in industrial-grade raw materials. This quantitative control of the proportion of molecules with specific functionalities ensures a more stable polymerization reaction activity and crosslinking rate within the system, providing a stable and predictable process window for the injection and curing of the prepolymer liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685804A_ABST
    Figure CN122685804A_ABST
Patent Text Reader

Abstract

The application provides a prepolymer solution and a preparation method thereof, a lithium battery and an electric device, and relates to the technical field of battery materials. The prepolymer solution comprises a liquid electrolyte, an initiator and a cross-linkable monomer composition; the mass fraction of pentaerythritol ester containing three acrylate groups in the molecular structure in the cross-linkable monomer composition is M, the mass fraction of pentaerythritol ester containing four acrylate groups in the molecular structure is N, and M+N is greater than or equal to 80%. The prepolymer solution provided by the application clearly defines the mass fraction of pentaerythritol ester with specific functionality and makes the sum not less than 80%, effectively reducing the interference of industrial raw material batch fluctuation. This not only helps to stabilize the curing process window, but also improves the consistency of the cross-linking network density, thereby endowing the gel polymer electrolyte with good reproducible ionic conductivity and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials technology, and more specifically, to a prepolymer liquid and its preparation method, a lithium battery, and an electrical device. Background Technology

[0002] In practical applications, traditional liquid electrolytes in lithium-ion batteries pose potential safety hazards such as leakage. Gel polymer electrolytes, as an alternative, can improve battery safety performance while retaining a certain ion transport capacity.

[0003] In the preparation of gel polymer electrolytes, in-situ curing technology has been widely used. This technology typically involves injecting a prepolymer solution containing crosslinkable monomers, initiators, and electrolytes into the battery, wetting the electrodes and separator, and then initiating polymerization to form a gel state. Among these, multifunctional acrylate monomers (such as pentaerythritol acrylates) are often used as crosslinkable monomers because they can form crosslinked network structures.

[0004] However, due to limitations in the esterification process, industrially produced multifunctional acrylate monomers are typically mixtures of products with different degrees of substitution. The distribution ratios of each functional component vary between different batches of industrial monomers. In existing technologies and practical operations, these fluctuations in internal component ratios are usually not differentiated; instead, they are used directly as single components, leading to disordered fluctuations in the reaction rate and crosslinking network density during polymerization between different batches of monomers.

[0005] The arbitrary and uncontrollable proportions of the components within the aforementioned monomers make it difficult to reproduce the properties of the final gel polymer electrolyte in terms of ionic conductivity and structural stability. Furthermore, fluctuations in the activity of the reaction system make it impossible to standardize process parameters such as curing time, increasing the complexity of the battery electrolyte injection and curing processes and hindering targeted improvements to the gel polymer electrolyte's performance.

[0006] In view of the above, this application is hereby submitted.

[0007] This application relates to the field of battery materials technology, and more specifically, to a prepolymer liquid and its preparation method, a lithium battery, and an electrical device. Summary of the Invention

[0008] The purpose of this application is to provide a prepolymer liquid and its preparation method, a lithium battery, and an electrical device. The prepolymer liquid, by limiting the mass fraction of monomers with specific functionalities, eliminates batch fluctuations in industrial raw materials, ensuring the stability of the curing process and the highly reproducible electrochemical performance of the gel electrolyte.

[0009] In order to achieve the above-mentioned objectives of this application, the following technical solution is adopted: In a first aspect, this application provides a prepolymer liquid, the prepolymer liquid comprising a liquid electrolyte, an initiator, and a crosslinkable monomer composition; In the crosslinkable monomer composition, the mass fraction of pentaerythritol ester containing three acrylate groups in the molecular structure is M, and the mass fraction of pentaerythritol ester containing four acrylate groups in the molecular structure is N, and the following condition is met: M+N≥80%; In an optional embodiment, the liquid electrolyte comprises a lithium salt and an organic solvent; and / or, The initiator is at least one of a photoinitiator and a thermal initiator.

[0010] In an optional embodiment, the initiator is used in an amount of 0.1% to 5% of the total mass of the crosslinkable monomer composition; and / or, The crosslinkable monomer composition is present in the prepolymer solution at a mass percentage of 1% to 20%; and / or, The liquid electrolyte has a mass percentage of 80% to 99% in the prepolymer solution.

[0011] In an optional embodiment, the mass fraction M is 25% to 55%; and / or, The mass fraction N is 45%~75%.

[0012] Secondly, this application provides an in-situ cured gel polymer electrolyte, which is formed by in-situ polymerization of the prepolymer liquid described in the foregoing embodiments inside the battery.

[0013] Thirdly, this application provides a method for preparing the prepolymer liquid as described in the foregoing embodiments, comprising: The actual mass fraction of pentaerythritol esters containing three and four acrylate groups in the various industrial-grade pentaerythritol mixed ester raw materials to be used was determined. Based on the target total mass fraction of pentaerythritol esters containing three and four acrylate groups in the preset molecular structure, the addition weight of each of the industrial-grade pentaerythritol mixed ester raw materials is calculated and adjusted using algebraic relationships, and the crosslinkable monomer composition is obtained after mixing. The prepared crosslinkable monomer composition is mixed with the liquid electrolyte and initiator to obtain the prepolymer solution.

[0014] In an optional embodiment, in the step of calculating and adjusting the added weight of each of the industrial-grade pentaerythritol mixed ester raw materials using algebraic relationships: When a first industrial-grade pentaerythritol mixed ester raw material with a weight of X and a second industrial-grade pentaerythritol mixed ester raw material with a weight of Y are mixed and formulated, the actual mass fractions of pentaerythritol esters containing three and four acrylate groups in the molecular structure of the first industrial-grade pentaerythritol mixed ester raw material are a% and b%, respectively; the actual mass fractions of pentaerythritol esters containing three and four acrylate groups in the molecular structure of the second industrial-grade pentaerythritol mixed ester raw material are c% and d%, respectively. Using the formulas respectively and The values ​​of X and Y are calculated and adjusted so that the actual total mass fraction of pentaerythritol esters containing three and four acrylate groups in the molecular structure of the crosslinkable monomer composition after mixing reaches the corresponding target total mass fraction.

[0015] Fourthly, this application provides a lithium battery, including a positive electrode, a negative electrode, a separator, and an in-situ cured gel polymer electrolyte as described in the foregoing embodiments.

[0016] Fifthly, this application provides an electrical device including a lithium battery as described in the foregoing embodiments.

[0017] Compared with existing technologies, the prepolymer liquid provided in this application precisely defines the molecular microstructure of the crosslinkable monomer composition, clearly specifying the mass fraction of pentaerythritol esters containing three and four acrylate groups, and strictly controlling their total to 80% or higher. This greatly suppresses the interference of component fluctuations caused by batch-to-batch differences in industrial-grade raw materials. This quantitative control of the proportion of molecules with specific functionalities ensures a more stable polymerization reaction activity and crosslinking rate within the system, providing a stable and predictable process window for the injection and curing of the prepolymer liquid.

[0018] Meanwhile, the stable presence of a specific number of acrylate groups ensures that the gel crosslinking network formed after in-situ polymerization has a highly consistent density. This uniform polymer network structure significantly alleviates the random fluctuations in electrochemical performance caused by microstructural disorder, enabling the final gel polymer electrolyte to exhibit relatively stable and reproducible ionic conductivity and excellent high-voltage stability. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0020] Figure 1 This is a liquid chromatography (HPLC) chromatogram of the crosslinkable monomer composition obtained by dynamic formulation in batch 1 of Example 1 of this application; Figure 2 These are comparative optical morphology photographs of batch 1 (target composition M=40%, N=60%) in Example 1 of this application and Comparative Example 4 (extremely low effective functionality, M+N=50%) after in-situ curing. Detailed Implementation

[0021] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of this application. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0022] This application provides a prepolymer liquid. The prepolymer liquid includes a liquid electrolyte, an initiator, and a crosslinkable monomer composition. In the crosslinkable monomer composition, the mass fraction of pentaerythritol ester containing three acrylate groups in its molecular structure is M, and the mass fraction of pentaerythritol ester containing four acrylate groups in its molecular structure is N, and the following condition is met: M+N≥80%.

[0023] It should be noted that the mass fractions M and N mentioned in this application refer to the mass percentage of pentaerythritol ester derivatives containing three or four acrylate groups in their molecular structure within the total mass of all the crosslinkable monomer compositions. The calculation method is as follows: [Total mass of all pentaerythritol derivatives derived from each raw material component that contain three (or four) acrylate groups in their molecular structure] ÷ (Total mass of the crosslinkable monomer composition) × 100%.

[0024] For the above-mentioned M+N mass fraction range, for example, it can be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 99%, 100%, etc.

[0025] In the aforementioned prepolymer system, the liquid electrolyte serves as the ion transport carrier, and the crosslinkable monomer composition serves as the reaction raw material for constructing the gel framework. Pentaerythritol esters containing three acrylate groups in their molecular structure possess three polymerizable carbon-carbon double bonds, while pentaerythritol esters containing four acrylate groups in their molecular structure possess four polymerizable carbon-carbon double bonds. Under the triggering action of an initiator, the aforementioned acrylate groups undergo free radical polymerization and crosslink with each other, constructing a three-dimensional polymer network. Simultaneously, the liquid electrolyte is solidified in situ and encapsulated within this three-dimensional polymer network, realizing the transformation from a liquid prepolymer to a gel polymer electrolyte.

[0026] By limiting the total mass fraction of pentaerythritol esters containing three acrylate groups and pentaerythritol esters containing four acrylate groups in the crosslinkable monomer composition to greater than or equal to 80%, the purity baseline of the high-functionality core crosslinking material in the system is clearly defined. This mass fraction definition eliminates the dilution and interference of low-functionality impurity components on the crosslinking density, ensuring a stable polymerization reactivity and degree of crosslinking in the system. This setting stabilizes the process window for gelation, ensuring the density and uniformity of the three-dimensional polymer network structure formed after curing.

[0027] In summary, this embodiment effectively eliminates component fluctuations caused by batch-to-batch variations in industrial raw materials by precisely defining the mass fractions of pentaerythritol esters containing three and four acrylate groups and controlling their total to be no less than 80%. This strict control over the proportion of molecules with specific functionalities not only ensures the stability of the polymerization reactivity and provides a predictable curing process window, but also guarantees the consistency of the crosslinking network density after in-situ polymerization, fundamentally eliminating random performance fluctuations and giving the gel polymer electrolyte highly reproducible ionic conductivity and structural stability.

[0028] In some embodiments, the liquid electrolyte includes lithium salt and organic solvent.

[0029] In the above system, the organic solvent serves as a dissociation medium, and the lithium salt dissolves in the organic solvent to provide freely migrating lithium ions, thereby imparting ionic conductivity to the system. After the prepolymer liquid undergoes in-situ polymerization to form a gel framework, the liquid phase composed of the lithium salt and the organic solvent is confined within a three-dimensional polymer network, ensuring the electrochemical transport performance of the system. The lithium salt can be any conventional conductive salt used in battery systems, and the organic solvent can be any conventional non-aqueous organic solvent. This embodiment does not impose excessive restrictions on these, in order to meet the needs of different electrochemical windows.

[0030] In some embodiments, the crosslinkable monomer composition is present in the prepolymer solution at a mass percentage of 1% to 20%. For example, it can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 19%, 20%, etc.

[0031] It should be noted that while the absolute amount of crosslinkable monomer added affects the initial viscosity of the prepolymer and the in-situ curing reaction rate (higher concentration, greater reaction site density, faster curing, and a denser final crosslinked network), it does not change the core mechanism by which this invention addresses batch stability. In this application, the core logic of batch stability lies in maintaining a strictly constant ratio of trifunctional to tetrafunctional components in the final monomer composition. Regardless of the mass percentage of the crosslinkable monomer composition in the prepolymer, as long as this ratio remains constant, the relative crosslinking density and network topology between batches under the same formulation will remain consistent, and performance fluctuations between batches can be controlled at a similarly low level. In other words, the absolute viscosity and absolute curing time will vary with the monomer mass percentage, but the relative standard deviation (RSD) between batches will not significantly increase due to concentration changes. This is determined by the technical logic of this invention: "composition determines performance, and formulation ensures composition."

[0032] Therefore, those skilled in the art can reasonably expect that, regardless of the specific percentage of 1% to 20% of the crosslinkable monomer composition added, excellent batch stability can be achieved at each concentration by employing the dynamic formulation method of the present invention.

[0033] In some embodiments, the initiator is at least one of a photoinitiator and a thermal initiator.

[0034] The initiator is used to generate free radicals under specific external energy conditions (light or heat), thereby initiating a chain polymerization reaction of acrylate double bonds in the crosslinkable monomer composition. Using a photoinitiator allows for rapid surface or shallow curing under light conditions; using a thermal initiator allows for deep and uniform curing inside the battery by penetrating non-transparent components using an external heat source. Employing at least one of these initiators provides flexible process matching options based on the actual battery encapsulation process and curing environment, ensuring the successful construction of the crosslinked network under different process conditions.

[0035] In some embodiments, the initiator is used in an amount of 0.1% to 5% of the total mass of the crosslinkable monomer composition. For example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, etc.

[0036] The mass ratio of each component in the system has a substantial impact on the final molding state and electrochemical performance of the gel polymer electrolyte. Controlling the amount of the initiator to 0.1%~5% of the total mass of the crosslinkable monomer composition can maintain a reasonable curing time while avoiding low polymer molecular weight and network structure defects caused by excessively rapid free radical generation. It also helps to reduce potential electrochemical side reactions caused by unreacted initiator residues.

[0037] Similar to the addition amount of monomeric compositions, since the amount of initiator added only affects the free radical generation rate and curing reaction kinetics (the higher the amount, the faster the curing), it will not disrupt the core logic chain of this invention regarding batch stability. Therefore, those skilled in the art can reasonably expect that regardless of any specific value of the initiator dosage from 0.1% to 5%, excellent batch stability can be achieved at each concentration by employing the dynamic formulation method of this invention. In some embodiments, the liquid electrolyte has a mass percentage of 80% to 99% in the prepolymer solution. For example, it can be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 97%, 98%, 99%, etc.

[0038] The mass percentage of the crosslinkable monomer composition in the prepolymer solution is controlled at 1%~20%, and the mass percentage of the liquid electrolyte is controlled at 80%~99% to achieve a better balance between mechanical rigidity and ion conduction channels. In-situ curing with 1%~20% of the monomer composition allows for the construction of a three-dimensional polymer network with sufficient binding force to prevent electrolyte leakage. Simultaneously, the retention of a high proportion of 80%~99% liquid electrolyte phase within the system avoids steric hindrance to lithium-ion migration caused by excessive network density, enabling the gel system to maintain excellent ionic conductivity after curing.

[0039] In some implementations, the mass fraction M is 25% to 55%. For example, it can be 25%, 26%, 30%, 35%, 38%, 42%, 45%, 49%, 52%, 55%, etc.

[0040] In some implementations, the mass fraction N is 45% to 75%. For example, it can be 45%, 48%, 53%, 58%, 63%, 68%, 73%, 75%, etc.

[0041] The ratio of molecules with specific functionalities in a crosslinkable monomer composition directly determines the spatial topology of the three-dimensional polymer network formed after in-situ curing. Pentaerythritol esters containing three acrylate groups tend to form relatively flexible crosslinking nodes with moderate free volume during polymerization; while pentaerythritol esters containing four acrylate groups tend to form highly dense and rigid crosslinking nodes during polymerization.

[0042] Maintaining the mass fraction N between 33% and 77%, and simultaneously controlling the mass fraction M between 23% and 55%, facilitates a better balance between crosslinking density and ion transport channels within the system. If the proportion of tetrafunctional molecules is too high or the proportion of trifunctional molecules is too low, the cured polymer network will become excessively dense, increasing the tortuosity of internal pores and thus hindering lithium-ion migration to some extent. Conversely, if the proportion of trifunctional molecules is too high and the proportion of tetrafunctional molecules is insufficient, the crosslinking network structure may become loose, weakening the gel system's physical binding ability to the liquid phase and its resistance to high-pressure oxidation. Limiting the mass fractions of both within the aforementioned specific ranges allows the prepolymer to cure and form a gel framework with suitable mechanical strength and excellent ionic conductivity while maintaining good wettability.

[0043] This application also provides an in-situ cured gel polymer electrolyte, which is formed by in-situ polymerization of the prepolymer liquid described in the foregoing embodiments inside the battery.

[0044] This gel polymer electrolyte comprises a three-dimensional polymer crosslinked network formed by free radical polymerization of a crosslinkable monomer composition, and a liquid electrolyte in situ confined within the pores of this three-dimensional polymer crosslinked network. In terms of preparation and molding mechanism, the prepolymer liquid is injected into the battery in a low-viscosity liquid state, which can fully penetrate and wet the pores of the electrode plates and separator. After physical wetting is completed, the system undergoes in-situ crosslinking and solidification under the action of an initiator, and the liquid component is in situ transformed into a gel state.

[0045] By performing in-situ polymerization inside the battery, the resulting gel polymer electrolyte can achieve molecular-level conformal contact with the electrode material surface, constructing a continuous and compact solid-liquid-solid interface transport channel, significantly reducing the charge transfer impedance at the interface. Furthermore, due to the strict control of the mass ratio of monomers with specific functionalities in the precursor prepolymer solution, the three-dimensional polymer network generated after in-situ curing exhibits excellent uniformity and density. This uniform network framework not only provides sufficient mechanical rigidity to prevent leakage of the liquid electrolyte but also maintains unobstructed microscopic ion migration channels, enabling the final gel polymer electrolyte to possess both excellent safety performance and highly stable electrochemical performance.

[0046] This application embodiment also provides a method for preparing the prepolymer liquid as described in the foregoing embodiments, comprising: Step S1: Determine the actual mass fraction of pentaerythritol esters containing three and four acrylate groups in the various industrial-grade pentaerythritol mixed ester raw materials to be used.

[0047] In actual industrial production, the industrial-grade pentaerythritol mixed ester raw materials obtained through esterification reactions are often not single pure substances, but rather mixed systems containing molecules with different degrees of substitution. The distribution ratio of molecules with different functionalities inherently varies between different batches or from different suppliers. In this step, a quantitative component analysis is performed on the industrial-grade raw materials used beforehand. The specific determination method is not strictly limited; for example, analytical chemistry methods such as high-performance liquid chromatography, gas chromatography-mass spectrometry, or nuclear magnetic resonance spectroscopy can be used to accurately quantify the true mass percentage of pentaerythritol esters containing exactly three acrylate groups and pentaerythritol esters containing four acrylate groups within the molecular structure of each industrial-grade raw material.

[0048] Step S2: Based on the target total mass fraction of pentaerythritol esters containing three and four acrylate groups in the preset molecular structure, the addition weight of each of the industrial-grade pentaerythritol mixed ester raw materials is calculated and adjusted using algebraic relationships, and the crosslinkable monomer composition is obtained after mixing.

[0049] After obtaining the actual purity data of each raw material, an algebraic relationship is established based on the principle of mass conservation. Specifically, the target total mass fraction of molecules with specific functionalities is set, and combined with the measured actual mass fractions of each raw material, the precise input weight of each group of industrial-grade raw materials is calculated by solving the algebraic relationship. According to the calculated added weight, the corresponding industrial-grade pentaerythritol mixed ester raw materials are weighed and physically mixed to obtain a crosslinkable monomer composition. Through this formulation step based on algebraic calculation, the influence of fluctuations in the internal component ratios of different batches of industrial-grade raw materials can be effectively offset, so that the proportion of core molecules with specific crosslinking activities in the final crosslinkable monomer composition converges to the preset target range.

[0050] Step S3: Mix the prepared crosslinkable monomer composition with the liquid electrolyte and initiator to obtain the prepolymer solution.

[0051] The crosslinkable monomer composition obtained through quantitative formulation is used as a backbone precursor and blended with a liquid electrolyte that acts as an ion conductor and an initiator that triggers polymerization. In practice, conventional methods such as mechanical stirring can be used to ensure that the components are fully miscible, forming a homogeneous liquid phase system. The prepolymer solution prepared in this step has uniform internal components and stable micro-molecular ratios between batches, and can be directly used for in-situ curing processes after injection into battery modules, thereby ensuring the high reproducibility of the electrochemical and mechanical properties of the gel polymer electrolyte.

[0052] In some embodiments, in step S2, the step of calculating and adjusting the added weight of each of the industrial-grade pentaerythritol mixed ester raw materials using algebraic relationships: The raw materials are mixed and formulated using a first industrial grade pentaerythritol mixed ester with a weight of X and a second industrial grade pentaerythritol mixed ester with a weight of Y. In the first industrial-grade pentaerythritol mixed ester raw material, the actual mass fractions of pentaerythritol esters containing three and four acrylate groups in their molecular structure are a% and b%, respectively. In the second industrial-grade pentaerythritol mixed ester raw material, the actual mass fractions of pentaerythritol esters containing three and four acrylate groups in their molecular structure are c% and d%, respectively. Using the formulas respectively and The values ​​of X and Y are calculated and adjusted so that the actual total mass fraction of pentaerythritol esters containing three and four acrylate groups in the molecular structure of the crosslinkable monomer composition after mixing reaches the corresponding target total mass fraction.

[0053] Specifically, using the formulas and Calculate and monitor the final proportion of specific molecules in the mixture. Among them, Used to characterize the actual total mass fraction of pentaerythritol esters containing three acrylate groups in the crosslinkable monomer composition after mixing; This is used to characterize the actual total mass fraction of pentaerythritol esters containing four acrylate groups in the crosslinkable monomer composition after mixing.

[0054] In actual blending operations, the preset target total mass fractions of pentaerythritol esters containing three and four acrylate groups are substituted into the two sets of algebraic formulas mentioned above as target constraint values. The weight ratio (i.e., the ratio of X to Y) of the first and second industrial-grade raw materials, satisfying the dual-target conditions, can be obtained through mathematical solutions. Physical blending is then performed according to this ratio.

[0055] This formulation process, based on algebraic relationships, transforms the multi-component mixing process into a precise linear solution process. By establishing a deterministic mathematical mapping relationship between the input (actual purity of industrial-grade mixed ester raw materials) and the output (purity of the target monomer composition), it is possible to dynamically offset the compositional fluctuations of different batches of industrial-grade mixed ester raw materials. This quantitative control method ensures that the formulated monomer composition has a stable functional distribution at the microscopic level, thus providing a reliable material basis for subsequently obtaining gel polymer electrolytes with uniform cross-linked network structures and stable electrochemical performance.

[0056] This application also provides a lithium battery, including a positive electrode, a negative electrode, a separator, and an in-situ cured gel polymer electrolyte as described in the foregoing embodiments.

[0057] In actual device structures, this lithium battery typically includes a positive electrode current collector, a negative electrode current collector, tabs for connecting to external circuits, and an outer packaging shell. The aforementioned in-situ cured gel polymer electrolyte is continuously distributed between the pores and interfaces of the electrode and separator, providing lithium-ion transport channels for the battery's charging and discharging process. The specific type and application scenario of this lithium battery are not strictly limited, and it can include, but is not limited to: semi-solid-state lithium-ion batteries, all-solid-state lithium batteries, polymer lithium batteries, or lithium metal batteries; in terms of packaging form, it can include, but is not limited to, pouch batteries, cylindrical batteries, prismatic batteries, or button batteries.

[0058] This application also provides an electrical device, including a lithium battery as described in the foregoing embodiments. The lithium battery serves as a power source or energy storage unit to provide the electrical energy required for the operation of the electrical device. Based on the excellent high-voltage stability and safety performance of the lithium battery, the electrical device can cover various types of electrically powered devices. Specifically, the electrical device may include, but is not limited to: consumer electronic terminals (e.g., smartphones, tablets, laptops, smart bracelets, smartwatches, etc.); new energy vehicles (e.g., pure electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, etc.); light power machinery (e.g., handheld power tools, drones, service robots, etc.); and other equipment systems with power supply requirements, such as portable energy storage power supplies, home or industrial-grade energy storage base stations, etc.

[0059] The present application is further illustrated below with specific embodiments. However, it should be understood that these embodiments are merely for the purpose of more detailed illustration and should not be construed as limiting the present application in any way.

[0060] Unless otherwise specified, the basic formulation and process for preparing the prepolymer solution in the following examples are as follows: 98g liquid electrolyte, 2g crosslinking monomer (the specific composition is described in each example and comparative example), and 0.03g azobisisobutyronitrile (initiator); wherein, the liquid electrolyte comprises 35g methyl ethyl carbonate, 19g ethylene carbonate, 15g propylene carbonate, 10g fluoroethylene carbonate, 1g propane sulpholactone, 2g ethylene sulfate, 10g lithium hexafluorophosphate, 4g lithium difluorosulfonylimide, 0.5g lithium difluorophosphate, and 0.5g lithium difluorooxalate borate. The above raw materials are mixed uniformly at room temperature, relative humidity below 2%, and dew point below -40°C to obtain the prepolymer solution.

[0061] The prepolymer liquid was placed in a hot oven and slowly heated to 50°C. The curing process was monitored every 30 minutes until a gel-like electrolyte that could be hung upside down without falling off was obtained, which proved that the in-situ thermosetting gel electrolyte preparation was complete.

[0062] Performance testing methods: (1) Monomer composition test: The pentaerythritol acrylate monomer components in the mixed ester raw materials and the blended composition were determined using a Shimadzu GTO-20A liquid chromatograph (Japan) according to GB / T 16631-2008 and HB / FB 03-2009 standards, employing the area normalization method to obtain the actual mass fraction of molecules with specific functionalities.

[0063] (2) Prepolymer viscosity test: The viscosity of the prepolymer solution was tested using an NDJ-5S digital rotary viscometer. The prepolymer solution was poured into a flat-bottomed container with a diameter greater than 60 mm, and the temperature was maintained at 25°C with a stable, vibration-free operating surface. Using an L0 rotor, it was slowly immersed in the prepolymer solution until the liquid level was flush with the rotor groove scale. After leveling the instrument, the rotor was started, and the viscosity value (unit: mPa·s) was read after the displayed value stabilized.

[0064] (3) Ionic conductivity test: The electrode rings for fixing the electrolyte and the polytetrafluoroethylene single ring acting as a container were placed at the bottom of the battery casing. Prepolymer samples prepared in each example and comparative example were dripped into the chamber to completely fill it. A stainless steel electrode plug was then placed on top to form a blocking electrode. The battery casing cover was then placed on top and tightened to complete the battery assembly. The assembled battery was directly connected to an electrochemical workstation (VMP-3e, Bio-Logic) and placed in a 50°C constant temperature oven for high-temperature curing. After curing, electrochemical impedance spectroscopy (EIS) tests were performed at frequencies from 1 MHz to 0.03 Hz. The ionic conductivity (σ, mS / cm) of the gel polymer electrolyte was calculated using the formula σ = L / (R×S), where L is the electrolyte thickness, S is the area of ​​the electrolyte membrane in contact with the electrode, and R is the impedance measured by the impedance meter.

[0065] Experimental Example 1: Batch stability verification of prepolymer solution and gel electrolyte Even when the total purity of industrially produced mixed ester feedstock meets the M+N≥80% requirement, the ratio of trifunctionality (M) to tetrafunctionality (N) within it still exhibits significant batch-to-batch fluctuations. Since pure triesters typically account for more than 50%, if the actual product requires a lower M value (e.g., target M=40%), or if it is necessary to eliminate the interference from fluctuations in single batches of feedstock, it is essential to determine the actual content of different batches of feedstock and use algebraic relationships to dynamically mix them with feedstocks rich in tetrafunctionality in order to achieve precise convergence of the final composition.

[0066] Therefore, this experimental example sets up Example 1, which uses dynamic allocation, and Comparative Example 1 and Comparative Example 2, which do not use dynamic allocation, for comparison.

[0067] 1. Example 1 (Dynamic Calculation and Allocation): The target composition was set as follows: M=40%, N=60% (M+N=100%). Raw material A, which is rich in trifunctionality, and raw material B, which is rich in tetrafunctionality, were selected. The composition was calculated for three fluctuating batches and mixed according to the calculated ratio (X:Y). The results are shown in Table 1.

[0068] Table 1. Actual and final performance of each batch of raw materials in Example 1

[0069] In batch 1, the calculated mixing mass ratio was 17:23, and the crosslinkable monomer composition was obtained by mixing according to this ratio. The liquid chromatogram of the crosslinkable monomer composition prepared in this batch is shown below. Figure 1 As shown, calculations show that M=40% and N=60% in the final monomer composition.

[0070] 2. Comparative Example 1 (fixed 2:3 mixing ratio, no dynamic adjustment): Using the same three batches of raw materials as in Table 1, they were uniformly mixed at a fixed ratio of 2:3 (that is, each batch of industrial raw materials was treated as a pure product for mixing).

[0071] Table 2. Results of fixed-mixing of each batch in Comparative Example 1

[0072] 3. Comparative Example 2 (Direct blind use of a single industrial raw material A): Use raw material A directly from the above three batches without mixing or blending.

[0073] Table 3. Results of Comparative Example 2 using a single raw material

[0074] Results Analysis: Tables 1, 2, and 3 show that in the prior art, intrinsic batch fluctuations of monomer raw materials (M content varying from 35% to 63%) directly lead to significant drift in key electrolyte parameters (curing time RSD as high as 16.7% to 15.7%). In Example 1 of this application, through dynamic formulation, despite approximately 8% fluctuation at the raw material level, the final product achieves precise convergence, with a stable curing time of 120 min (RSD=0%) and a stable conductivity of 6.53 mS / cm (RSD<0.15%), significantly improving the problem of poor performance reproducibility of gel polymers in the industry.

[0075] Experimental Example 2: Designability Verification of Prepolymer Solution and Electrolyte Performance The performance of gel electrolytes depends on the synergistic ratio of monomers with different functionalities. This experimental example verifies the adjustable boundaries of various physicochemical parameters by fixing the same batch of raw materials and adjusting the M / N ratio in the final composition.

[0076] Table 4. Performance of Gradients with Different M / N Ratios in Examples 2-6

[0077] Results Analysis: Table 4 reveals the following patterns: the viscosity of the prepolymer solution is continuously adjustable within the range of 4.40–5.50 mPa·s by adjusting the ratio of high to low functionality; the curing time is negatively correlated with the content of high functionality (tetraester), providing ample process adjustment window for battery manufacturing; and the ionic conductivity is positively correlated with the content of low functionality (triester). This indicates that those skilled in the art can reverse engineer and lock in the M content range of the monomer based on the target conductivity (e.g., requirement >6.6 mS / cm).

[0078] Experimental Example 3: Boundary Validation of the Lower Limit of Total Purity (M+N) for Specific Functionalities Some raw materials industrially labeled as pentaerythritol triacrylate actually contain a large amount of low-substituted or inert byproducts other than the triacrylate and tetraacrylate. This experiment investigated the hazards when the total M+N ratio was not up to standard.

[0079] 1. Comparative Example 3 (M+N fluctuates between 70% and 80%, and is dynamically adjusted): Raw materials A' and B', which contain a large amount of other byproducts, are selected, and their total M+N content is only 68%~76%.

[0080] Table 5. Blending results of Comparative Example 3 containing higher impurities.

[0081] 2. Comparative Example 4 (Extreme verification, M+N as low as 50%) Products A'' and B'' were selected, and after mixing, the system contained M=15%, N=35% (M+N=50%), and other low-functionality components accounted for 50%. Tests showed that the prepolymer viscosity was 4.7 mPa·s, and the gelation time was >1200 min. Figure 2 As can be seen (A in the figure is Example 1, B is Comparative Example 4), the product of Comparative Example 4 after polymerization is a paste-like liquid that cannot form an effective gel.

[0082] Results Analysis: As shown in Table 5 and Comparative Example 4, when M+N < 80% and contains a large amount of inert or low-crosslinking active components, even if the final M and N ratio is made extremely consistent through dynamic adjustment (M content RSD as low as 0.40%), the curing time (RSD up to 20%) and conductivity of the final gel electrolyte will still show serious uncontrollable drift, and in severe cases, it may even be impossible to form a gel. This verifies from the opposite perspective that limiting 'M+N ≥ 80%' in this application is a key condition for reducing impurity interference and ensuring the quality of polymer network molding.

Claims

1. A prepolymer liquid, characterized in that, The prepolymer solution comprises a liquid electrolyte, an initiator, and a crosslinkable monomer composition; In the crosslinkable monomer composition, the mass fraction of pentaerythritol ester containing three acrylate groups in the molecular structure is M, and the mass fraction of pentaerythritol ester containing four acrylate groups in the molecular structure is N, and satisfies: M+N≥80%.

2. The prepolymer liquid as described in claim 1, characterized in that, The liquid electrolyte comprises lithium salt and organic solvent; and / or, The initiator is at least one of a photoinitiator and a thermal initiator.

3. The prepolymer liquid as described in claim 1, characterized in that, The amount of the initiator is 0.1% to 5% of the total mass of the crosslinkable monomer composition; and / or, The crosslinkable monomer composition is present in the prepolymer solution at a mass percentage of 1% to 20%; and / or, The liquid electrolyte has a mass percentage of 80% to 99% in the prepolymer solution.

4. The prepolymer liquid as described in claim 1, characterized in that, The mass fraction M is 25%~55%; and / or, The mass fraction N is 45%~75%.

5. An in-situ cured gel polymer electrolyte, characterized in that, The prepolymer is formed by in-situ polymerization inside the battery from the prepolymer liquid described in any one of claims 1-4.

6. A method for preparing the prepolymer liquid according to any one of claims 1-4, characterized in that, include: The actual mass fraction of pentaerythritol esters containing three and four acrylate groups in the various industrial-grade pentaerythritol mixed ester raw materials to be used was determined. Based on the target total mass fraction of pentaerythritol esters containing three and four acrylate groups in the preset molecular structure, the addition weight of each of the industrial-grade pentaerythritol mixed ester raw materials is calculated and adjusted using algebraic relationships, and the crosslinkable monomer composition is obtained after mixing. The prepared crosslinkable monomer composition is mixed with the liquid electrolyte and initiator to obtain the prepolymer solution.

7. The method for preparing the prepolymer liquid as described in claim 6, characterized in that, In the step of calculating and adjusting the added weight of each of the aforementioned industrial-grade pentaerythritol mixed ester raw materials using algebraic relationships: The raw materials are mixed and formulated using a first industrial grade pentaerythritol mixed ester with a weight of X and a second industrial grade pentaerythritol mixed ester with a weight of Y. In the first industrial-grade pentaerythritol mixed ester raw material, the actual mass fractions of pentaerythritol esters containing three and four acrylate groups in their molecular structure are a% and b%, respectively. In the second industrial-grade pentaerythritol mixed ester raw material, the actual mass fractions of pentaerythritol esters containing three and four acrylate groups in their molecular structure are c% and d%, respectively. Using the formulas respectively and The values ​​of X and Y are calculated and adjusted so that the actual total mass fraction of pentaerythritol esters containing three and four acrylate groups in the molecular structure of the crosslinkable monomer composition after mixing reaches the corresponding target total mass fraction.

8. A lithium battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an in-situ cured gel polymer electrolyte as described in claim 5.

9. An electrical appliance, characterized in that, Including the lithium battery as described in claim 8.